Arctic Cirrus Clouds: A Comparison of Properties Derived from Measurements by Ground-Based and Spaceborne Lidar Systems - Hanssen, Ingrid Margrethe Vestnes (UiT Norges arktiske universitet, 2015)
The purpose of this thesis is to investigate Arctic cirrus clouds. In this work, data from the ground-based lidar system at ALOMAR, Andøya Space Center. and the spaceborne lidar onboard the CALIPSO satellite is used. Cirrus clouds are an important factor in modeling climate changes, which is one of the major research fields of this time. Most of the cirrus cloud research concentrates on investigating the phenomenon in the tropical regions as some of the generating mechanisms of cirrus clouds are more common there. The study of cirrus clouds in the Arctic has been sparse due to lack of instrumentation. The ALOMAR facility offers instrumentation and database suitable for such research. Two lidar systems with similar properties are used in the thesis. The stationary system at Ramnan, Norway (379 meter above sea-level) has been in operation since 2005, and gives access to long-term data. The system measures the troposphere with good quality up to 15-20 km, and can also detect major events in the stratosphere up to 61 km. The CALIPSO satellite was launched in 2006 and has been operating steadily since 2007. The satellite orbits sun-synchronously, with two daily overpasses near Andøya. The onboard lidar has the same capabilities as the stationary system in Northern Norway, and the two datasets can be compared. Analysis of the data indicate that there is around 50% cirrus clouds in the Arctic region, with CALIPSO registering 48% and the ALOMAR Troposphere lidar finding 56%. Mean base height is found to be between 6600-7000 me- ters above sea-level for the two systems and clouds are relatively thin with a mean thickness of 1166 and 1464 meters for ALOMAR and CALIPSO, respec- tively. In tropical regions, base heights of 8-10 km and thickness of 2-3 km are common. Several interesting cases of cirrus clouds near the stratosphere are detected over ALOMAR. These cases require special attention, and indicate that cirrus clouds reside at higher altitudes than expected in the Arctic region.